Virulent Drexlervirial Bacteriophage MSK, Morphological and Genome Resemblance With Rtp Bacteriophage Inhibits the Multidrug-Resistant Bacteria - Khan, Muhammad Saleem Iqbal; Gao, Xiangzheng; Liang, Keying; Mei, Shengsheng; Zhan, Jinbiao (Frontiers in Microbiology, 2021)
Phage-host interactions are likely to have the most critical aspect of phage biology. Phages are the most abundant and ubiquitous infectious acellular entities in the biosphere, where their presence remains elusive. Here, the novel Escherichia coli lytic bacteriophage, named MSK, was isolated from the lysed culture of E. coli C (phix174 host). The genome of phage MSK was sequenced, comprising 45,053 bp with 44.8% G + C composition. In total, 73 open reading frames (ORFs) were predicted, out of which 24 showed a close homology with known functional proteins, including one tRNA-arg; however, the other 49 proteins with no proven function in the genome database were called hypothetical. Electron Microscopy and genome characterization have revealed that MSK phage has a rosette-like tail tip. There were, in total, 46 ORFs which were homologous to the Rtp genome. Among these ORFs, the tail fiber protein with a locus tag of MSK_000019 was homologous to Rtp 43 protein, which determines the host specificity. The other protein, MSK_000046, encodes lipoprotein (cor gene); that protein resembles Rtp 45, responsible for preventing adsorption during cell lysis. Thirteen MSK structural proteins were identified by SDS-PAGE analysis. Out of these, 12 were vital structural proteins, and one was a hypothetical protein. Among these, the protein terminase large (MSK_000072) subunit, which may be involved in DNA packaging and proposed packaging strategy of MSK bacteriophage genome, takes place through headful packaging using the pac-sites. Biosafety assessment of highly stable phage MSK genome analysis has revealed that the phage did not possess virulence genes, which indicates proper phage therapy. MSK phage potentially could be used to inhibit the multidrug-resistant bacteria, including AMP, TCN, and Colistin. Further, a comparative genome and lifestyle study of MSK phage confirmed the highest similarity level (87.18% ANI). These findings suggest it to be a new lytic isolated phage species. Finally, Blast and phylogenetic analysis of the large terminase subunit and tail fiber protein put it in Rtp viruses’ genus of family Drexlerviridae.